Endothelial activation and damage as a common pathological substrate in different pathologies and cell therapy complications - Palomo, Marta; Moreno-Castaño, Ana Belén; Salas, María Queralt; Escribano-Serrat, Silvia; Rovira, Montserrat; Guillen-Olmos, Elena; Fernandez, Sara; Ventosa-Capell, Helena; Youssef, Lina; Crispi, Fatima; Nomdedeu, Meritxell; Martinez-Sanchez, Julia; et al. (Frontiers in Medicine, 2023)
The endothelium is a biologically active interface with multiple functions, some of them common throughout the vascular tree, and others that depend on its anatomical location. Endothelial cells are continually exposed to cellular and humoral factors, and to all those elements (biological, chemical or hemodynamic) that circulate in blood at a certain time. It can adapt to different stimuli but this capability may be lost if the stimuli are strong enough and/or persistent in time. If the endothelium loses its adaptability it may become dysfunctional, becoming a potential real danger to the host. Endothelial dysfunction is present in multiple clinical conditions, such as chronic kidney disease, obesity, major depression, pregnancy-related complications, septic syndromes, COVID-19, and thrombotic microangiopathies, among other pathologies, but also in association with cell therapies, such as hematopoietic stem cell transplantation and treatment with chimeric antigen receptor T cells. In these diverse conditions, evidence suggests that the presence and severity of endothelial dysfunction correlate with the severity of the associated disease. More importantly, endothelial dysfunction has a strong diagnostic and prognostic value for the development of critical complications that, although may differ according to the underlying disease, have a vascular background in common. Our multidisciplinary team of women has devoted many years to exploring the role of the endothelium in association with the mentioned diseases and conditions. Our research group research group has characterized some of the mechanisms and also proposed biomarkers of endothelial damage. A better knowledge would provide therapeutic strategies either to prevent or to treat endothelial dysfunction.